2002
DOI: 10.1097/00005537-200210000-00005
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Magnetic Resonance Imaging of Human Cochlea

Abstract: Data established through the acquisition of images from cadaver cochlea, facial nerve, and vestibular complex provide a foundation for developing steps for testing temporal bones and, eventually, patients with Meniere's disease and other inner ear disease. The present ongoing project will provide information on baseline images of the inner ear using high-resolution MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…This phenomenon is very common at high field and indeed forms the basis for visualization of many structures whose physical size is subpixel, such as iron-loaded microglia and plaques in patients with Alzheimer disease. This phenomenon is supported by the findings of Silver et al, 5 who reported visualization of this structure at 9.4T MR imaging. We note that there are several discrepancies in this article with respect to the claimed spatial resolution, which does not agree with the image acquisition parameters in the "Materials and…”
supporting
confidence: 82%
“…This phenomenon is very common at high field and indeed forms the basis for visualization of many structures whose physical size is subpixel, such as iron-loaded microglia and plaques in patients with Alzheimer disease. This phenomenon is supported by the findings of Silver et al, 5 who reported visualization of this structure at 9.4T MR imaging. We note that there are several discrepancies in this article with respect to the claimed spatial resolution, which does not agree with the image acquisition parameters in the "Materials and…”
supporting
confidence: 82%
“…In excised human (3) and animal (4,5) inner ear cadaveric samples, voxel resolutions of 32 3 43 3 49 lm , 58 3 58 3 300 lm 3 have been achieved at 9.4 T, 7 T, and 4.7 T, respectively. The highest reported resolution for in vivo human cochlear imaging is nearly 300 lm isotropic at 3T.…”
Section: Introductionmentioning
confidence: 99%
“…Gadolinium enhancement has been a primary tool for improving inner ear imaging both in cadaveric samples (3,9) and in vivo human studies (2,10). The cadaveric studies have achieved direct visualization of the vestibular (Reissner's) membrane, the thin partition separating the perilymph containing scala vestibule, and endolymph containing scala media (3,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the latter can be seen routinely on CT images, visualizing the endolymphatic duct/vestibular aqueduct complex is extremely problematic, even where highest-resolution clinical MRI is used. Currently, ex vivo anatomic techniques are required to provide information on baseline images of the inner ear as seen on clinical high-resolution MRI scans [5]. By means of clinical imaging, pathology can at least be inferred from distortions of the above-mentioned landmarks.…”
mentioning
confidence: 99%